Hubungan Kepribadian Tangguh dan Optimisme dengan Stres Akademik pada Siswa SMA Negeri 1 Binjai - Aisyah, Dara; Hasanuddin, Hasanuddin; Munir, Abdul (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This study aims to determine the correlations of hardiness personality and optimism with academic stress in students of SMA Negeri 1 Binjai. Academic stress is the emotional tension that arises from life events at school and feelings of threatened student safety or self-esteem. The hypothesis proposed in this study is that there is a negative correlations of hardiness personality and optimism with academic stress, The type of research is quantitative, which is a study that emphasizes its analysis on numerical data or numbers, a sample of 95 students. The data collection method uses the hardiness personality scale and optimism and the academic stress scale. Data analysis using multiple regression analysis, the results obtained by Rxy) = -0.728 with p = 0.000 < 0.050, this shows that there is a significant correlations of hardiness personality and optimism with academic stress, thus the hypothesis proposed is accepted. The contribution of resilient personality and optimism to academic stress is =53%, meaning that there are still 47% more factors that affect academic stress that are not seen in this study, namely factors of self-esteem, intelligence, problem solving, and self-efficacy of the sources of stress experienced by students including the desire to achieve achievements, and external factors while factors that can reduce stress are ridha with God's provisions,Â  gratitude, positive thinking and dhikr (religiosity).